OHS Compliance and Motivation in Enhancing Productivity Through Competence: An Empirical Study on Low Cost Apartment Construction Projects in Aceh Province - Tuasikal, Bahaudin; Amin, Mawardi (Politeknik Sukabumi, 2025)
This study is an empirical quantitative-explanatory research that aims to examine the role of compliance with Occupational Health and Safety (OHS) regulations and work motivation in improving worker productivity, both directly and indirectly through work competence as an intervening variable. The research was conducted on a low-cost apartment construction project in Aceh Province between October and December 2024. Data were gathered using a structured questionnaire administered to 170 construction workers, with each respondent assessing latent variable indicators on a five-point Likert scale. The data were analyzed using the Structural Equation Modeling (SEM) approach with AMOS version 22.0. Due to the initial sample size being below the minimum threshold, a bootstrapping technique was applied 30 times, resulting in 200 observations. The findings reveal that compliance with OHS implementation and work motivation both have a significant and positive direct impact on productivity. Furthermore, OHS compliance and motivation also significantly enhance worker competence. Work competence plays a mediating role in the relationship between OHS compliance and productivity, as well as between motivation and productivity, although the mediation effect is relatively modest. Consequently, work competence is classified as a quasi-intervening variable. These results underscore the critical importance of OHS program implementation and motivation enhancement strategies in driving worker productivity, particularly in the construction sector.